POLA KOMUNIKASI PENGASUH DALAM MEMBINA AKHLAK ANAK ASUH DI PANTI ASUHAN AL-MUNAWWARAH CABANG PILAR DESA GENENG KABUPATEN NGAWI - Firdaus, Nida’ Majidatul; Abdurrazaq, Muhammad N. (Journal of Islamic Studies, 2023)
The purpose of the research on the topic of caregiver communication patterns in fostering the morals of foster children at the Al-Munawwarah Orphanage is to find out how parents or caregivers of the Al-Munawwarah Orphanage can use good communication patterns or models towards foster children, especially in fostering the morals of their foster children and what are the obstacles experienced by caregivers in fostering the morals of foster children. The data collection technique in this qualitative research was in-depth interviews with caregivers and several foster children at the Al-Munawwarah Orphanage, as well as observing the daily activities of the children in the orphanage. The results showed that there were two patterns of communication used by caregivers in fostering the morals of foster children, namely the wheel pattern and the chain pattern. The wheel pattern is the pattern that directs all information to the individual (foster child) conveyed by the caregiver. The chain pattern is a pattern that spreads or caregiver A communicates to foster B, B to foster C and so on. Both of these patterns function together to provide direction or good moral development to children. The inhibiting factors in fostering the morals of foster children are the characteristics or personality of the child itself, then the level of language between the child and the caregiver which is difficult to understand, and the noisy environment because it is close to a the boulevard.